Zircon U-Pb, whole-rock Rb-Sr and K-Ar ages of metamorphosed and metasomatized paleosol at the base of the Paleoproterozoic Aravalli Supergroup, NW India: A two-billion-year record of tectono-thermal events. (1st May 2023) - Sreenivas, Bulusu; Vijaya Kumar, T.; Babu, E.V.S.S.K.; Bhaskar Rao, Y.J.; Chugaev, A.V.; Lebedev, V.A.; Vrevsky, A.B.
Graphical abstract: Highlights: Thermal events recorded by the Aravalli paleosol are dated. Paleosol zircons yielded Neoarchean ages similar to parent granite. Pb-Pb and Rb-Sr ages reveal Paleo- and Mesoproterozoic metamorphic and metasomatic events. Rare earth elements mobilized during K-metasomatism. Paleosols are effective markers of tectono-thermal events in the Preambrian terranes. Abstract: The Precambrian paleosols are good proxies for deciphering paleoredox conditions. They are also good indicators of thermal events that affect the metamorphic terrane. The Rb-Sr isochron ages of the Precambrian paleosols are good indicators of the timing of alkali metasomatism. This work presents zircon U-Pb, whole-rock Rb-Sr isochron, and K-Ar ages of a metamorphosed and metasomatized paleosol occurring at the base of the Paleoproterozoic Aravalli Supergroup, Northwestern India, to constrain the time of major thermal events. The Aravalli paleosols (sericite schists) have witnessed a complex history of metamorphism and metasomatism. The LA-ICP-MS U-Pb ages of zircons from the two paleosol samples are 2586 ± 45 Ma and 2793 ± 21 Ma, similar to the zircon ages for the parent Ahar River Granite. Five paleosol samples define an Rb-Sr isochron age of 1394 ± 22 Ma with ( 87 Sr/ 86 Sr)i of 0.7493 ± 0.0034 (2σ) and an MSWD of 3.9, pointing to the timing of the latest alkali metasomatism affecting the paleosols. The whole-rock K-Ar ages of sericite-rich paleosol samples range from 940 ± 30 to 873 ± 25 Ma, corresponding with the emplacement of Erinpura Granite. Thus, the Aravalli paleosol recorded more than two billion years of thermal events in its multi-geochronometers. The correlation between Rb-Sr isotope compositions and REE contents in paleosol samples suggests the REE mobility during K-metasomatism.